Reliable high risk HPV DNA testing by polymerase chain reaction: an intermethod and intramethod comparison. Issue 7 (1st July 1999) - Jacobs, M V; Snijders, P J; Voorhorst, F J; Dillner, J; Forslund, O; Johansson, B; von Knebel Doeberitz, M; Meijer, C J; Meyer, T; Nindl, I; Pfister, H; Stockfleth, E; et al.
Abstract : BACKGROUND: The development of a reproducible, sensitive, and standardised human papillomavirus (HPV) polymerase chain reaction (PCR) test is required to implement HPV testing in cervical cancer screening programmes and for triaging women with mild to moderate dysplasia. AIMS: To determine the intermethod agreement between different GP5+/6+ and MY09/11 PCR based protocols for the detection and typing of high risk (HR) HPV DNA in cervical smears and to assess the intramethod reproducibility of the GP5+/6+ PCR enzyme immunoassay (EIA) for HR-HPV detection. METHODS: For the intermethod comparison, crude aliquots of 20 well characterised cervical smears comprising five HPV negative samples, and six and nine samples containing single and multiple HPV infections, respectively, were coded and sent from reference laboratory (A) to three other laboratories. One of these (laboratory B) used the GP5+/6+ PCR-EIA and was provided with standard protocols. Another laboratory (C) used GP5+/6+ PCR combined with sequence analysis and type specific PCR, whereas two laboratories (D and E) used MY09/11 PCR followed by restriction fragment length polymorphism (RFLP) analysis for the detection and typing of HR-HPV. The intramethod agreement of GP5+/6+ PCR-EIA was analysed in a subsequent study with four other laboratories (F to I) on crude aliquots of 50 well characterised cervical smears, consisting of 32 HR-HPV positive and 18 HPV negative samples. Standardised protocols, primers, and probes were also provided by the reference laboratory for HR-HPV detection. RESULTS: In the intermethod comparison, pairwise agreement of the different laboratories with reference laboratory A for the detection of HR-HPV varied between 75% and 100% (kappa values: 0.5 to 1). Typing data revealed a broader range in pairwise agreement rates between 32% and 100%. The highest agreement was found between laboratories A and B using standardised protocols and validated reagents. In the intramethod evaluation, pairwise comparison of the laboratories F to I with reference laboratory A revealed excellent agreement rates from 92% to 100% (kappa values: 0.88 to 1.0) with an overall sensitivity of 97.5% (195/200) and specificity of 99.5% (199/200). CONCLUSIONS: The detection of HR-HPV as a group is highly reproducible with GP5+/6+ PCR-EIA provided that standardised protocols and validated reagents are used.